Validation, kinetic modeling, and test-retest reproducibility of [18F]SynVesT-1 for PET imaging of synaptic vesicle glycoprotein 2A in mice. Issue 10 (October 2022) - Bertoglio, Daniele; Zajicek, Franziska; Lombaerde, Stef De; Miranda, Alan; Stroobants, Sigrid; Wang, Yuchuan; Dominguez, Celia; Munoz-Sanjuan, Ignacio; Bard, Jonathan; Liu, Longbin; Verhaeghe, Jeroen; Staelens, Steven
Alterations in synaptic vesicle glycoprotein 2 A (SV2A) have been associated with several neuropsychiatric and neurodegenerative disorders. Therefore, SV2A positron emission tomography (PET) imaging may provide a unique tool to investigate synaptic density dynamics during disease progression and after therapeutic intervention. This study aims to extensively characterize the novel radioligand [ 18 F]SynVesT-1 for preclinical applications. In C57Bl/6J mice ( n = 39), we assessed the plasma profile of [ 18 F]SynVesT-1, validated the use of a noninvasive image-derived input function (IDIF) compared to an arterial input function (AIF), performed a blocking study with levetiracetam (50 and 200 mg/kg, i.p.) to verify the specificity towards SV2A, examined kinetic models for volume of distribution ( V T ) quantification, and explored test-retest reproducibility of [ 18 F]SynVesT-1 in the central nervous system (CNS). Plasma availability of [ 18 F]SynVesT-1 decreased rapidly (13.4 ± 1.5% at 30 min post-injection). V T based on AIF and IDIF showed excellent agreement (r 2 = 0.95, p < 0.0001) and could be reliably estimated with a 60-min acquisition. The blocking study resulted in a complete blockade with no suitable reference region. Test-retest analysis indicated good reproducibility (mean absolute variability <10%). In conclusion, [ 18 F]SynVesT-1 is selective for SV2A with optimal kinetics representing a candidate tool to quantify CNS synaptic density non-invasively.